Factors influencing electronic commerce adoption in Malaysian small and medium sized enterprises (SMES) / Fatima Ajmal - Fatima , Ajmal (2017)
Electronic commerce (E-commerce) plays an important role in growth of Small and medium-sized enterprises (SMEs) as it allow them compete efficiently in both domestic and international markets. This study identifies factors that influence adoption of e-commerce in SMEs, in order to formulate a proposed model for e-commerce. These factors act as a set of guidelines that are needed by SMEs for the successful and comprehensively secure implementation of e-commerce within their businesses. This study uses the IS success model by Molla and Licker (2001), as the basis for this research. The model proposes a partial extension and respecification of the Delone and McLean model of IS success for e-commerce systems. It is posited that e-commerce system quality, content quality, trust, and support services, effect the use and customer satisfaction that leads to e-commerce success. The factors of the IS success model are included in the proposed holistic model. The case study uses data collected from five different Malaysian SME industries. The study adopts an explanatory mixed-method approach (i.e., using questionnaires, interviews, and observation); where data is collected from both business owners and Chief Executive Officers (CEO). The two study groups involved in this study are the government based organization - SME Corporation (SMEcorp), and the non-government organization – namely the Association of Bumiputra Women Entrepreneur Network of Malaysia (WENA). Descriptive statistics are created to verify the factors for a secure and successful adoption of e-commerce within SMEs. Transactional security, loyalty, intellectual property rights, and implementation factors, are deemed to be the most important elements needed for the success of B2C e-commerce in Malaysia. The conceptual model is then verified using the Confirmatory Factor Analysis (CFA) of AMOS; where the 32 factors that were collected during the literature review were verified to both develop and confirm the model. This model is later validated by conducting interviews and observations with SMEs. The prototype system is developed based on a model for e-commerce evaluated by SME managers, CEOs, and business owners during focus group sessions. This study contributes to existing knowledge by studying success factors including security factors to develop a holistic e-commerce model that can be implemented in SMEs belonging to any five industries. In the future, this model can be further tested in different regions and countries to further verify its validity.